The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18697/ajfand.73.14095
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Determinants of Tissue Culture Banana Adoption in Western Kenya

Abstract: In this study cross-section data was used to analyze the effect of farmers' demographic, socioeconomic and institutional setting, market access and physical attributes on the probability and intensity of tissue culture banana (TCB) adoption. The study was carried out between July 2011 and November 2011. Both descriptive (mean, variance, promotions) and regression analysis were used in the analysis. A double hurdle regression model was fitted on the data. Using multistage sampling technique, four counties and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Eight studies in this category focused on the adoption of improved varieties in all five main RTB crops in Africa (Abebe et al 2013;Afolami et al 2015;Deffo and Demo 2003;Edmeades et al 2007;Nigussie et al 2016;Tarawali et al 2012). In addition, we identified studies on the adoption of planting material from rapid, disease-free propagation methods, such as tissue-culture bananas in Kenya (Wanyama et al 2016) and tissue-culture sweet potatoes in Zimbabwe (Mutandwa et al 2008), certified seed potatoes marketed by a private seed company in Kenya (Okello et al 2016). While the majority of studies focused on the adoption of certain varieties, four of the identified studies (Abebe et al 2013;Edmeades and Smale 2006;Okello et al 2016;Wanyama et al 2016) also studied the intensity of adoption; the amount of seed and area of land that adopting farmers used for cultivation.…”
Section: Characterization Of (Non-)adopters (N = 11)mentioning
confidence: 99%
“…Eight studies in this category focused on the adoption of improved varieties in all five main RTB crops in Africa (Abebe et al 2013;Afolami et al 2015;Deffo and Demo 2003;Edmeades et al 2007;Nigussie et al 2016;Tarawali et al 2012). In addition, we identified studies on the adoption of planting material from rapid, disease-free propagation methods, such as tissue-culture bananas in Kenya (Wanyama et al 2016) and tissue-culture sweet potatoes in Zimbabwe (Mutandwa et al 2008), certified seed potatoes marketed by a private seed company in Kenya (Okello et al 2016). While the majority of studies focused on the adoption of certain varieties, four of the identified studies (Abebe et al 2013;Edmeades and Smale 2006;Okello et al 2016;Wanyama et al 2016) also studied the intensity of adoption; the amount of seed and area of land that adopting farmers used for cultivation.…”
Section: Characterization Of (Non-)adopters (N = 11)mentioning
confidence: 99%
“…Market accessibility by farmers is important in technology adoption through input acquisition and product sales. Distance from the market raises transaction costs and markedly decimates farmers' profit margins [25].…”
Section: Factors Influencing Banana Farming In Kisii Nyamira and Embumentioning
confidence: 99%
“…e significant correlation at 0.01 level of access farm management training and accessing TC banana seedling suggests that training has a vital role in information disseminating. Contact with extension officers has been reported to have a positive effect on the adoption of agriculture technology by farmers, and this is based on innovation diffusion theory [25]. When farmers are exposed to the available information, it stimulates adoption of a technology [26].…”
Section: Banana Tissue Culture Technology Adoptionmentioning
confidence: 99%
See 2 more Smart Citations